Challenges of Vaccinations in the Era of New Media Communication. Issue 2 (April 2018) - Jung, Minsoo
Abstract : Active discussions are underway on whether or not the absence or insufficiency of communication is a decisive factor affecting hesitancy with regard to vaccines. Low-quality services such as insufficient communication can lead to an increase in the population postponing vaccinations in countries without deficiencies in vaccine procurement. This study examines the strategies and tasks of health communication in relation to vaccinations. Social networking services (SNSs) are major channels of health communication in responding to infectious diseases. New videos posted on the Internet attract considerable amounts of attention from SNS users and increase traffic to certain Web sites. However, most of these videos are produced and uploaded by nonexperts. Although medical institutions have striven to convey key messages concerning infectious diseases to the public, in the SNS space, contents differing from scientific evidence acknowledged as the established theory have been disseminated as well. Social networking services can also amplify any unnecessary anxiety about infectious diseases. In addition, as false information about vaccines is circulated or conflicting information surfaces, the confusion of the general public is aggravated and the phenomenon of vaccine hesitancy can be intensified. Therefore, it is necessary to improve vaccination acceptance through strategies that integrate new and old media. At the same time, we need to establish customized public health education for the public, vulnerable groups, and experts.